PERANAN KEARIFAN LOKAL (LOCAL WISDOM) DALAM PENGEMBANGAN EKONOMI DAN PERBANKAN SYARIAH DI INDONESIA - Akhmad Mujahidin (Institut Agama Islam Negeri Batusangkar, 2017)
In the context of urban Indonesia economic community, several terms, such as paroan, prapatan, dan pertelon are quite popolar. Such terminology has influence economic activities whic have become tradition that supports profit sharing principles which is practiced by sharia banking. Such profit sharing practices basically aimes at creating justice and provide balances for economic users and their environments. Furthermore, profit sharing practices show partnership relation among enterprise practitioners; more than just the relationship between superiors and subordinators. This kind of spirit does not end in profit oriented only but also establishing human based relationship which aimes at helping and caring one another. Dealing with the nature of the sprit above, sharia economic practitioners should have been energized and inspired and able to realize them in more real and synergical economic relationship. However, one important thing that they usually forget in developing business institution is lack of understanding toward the culture of the society where they build business, including sharia banking. Understanding toward local culture and wisdom of the society is one of the significant factors required in designing, harmonizing, and developing business. This implies that a busines institution should not aim at corporate oriented only. Infact, it should have relations of socio-culture) and coorporate social responsibility.